2011
DOI: 10.1007/s00276-011-0848-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent trigeminal artery and its variants on MR angiography

Abstract: On MR angiography, the incidence of PTA was 0.34% and of PTA variants, 0.17%. Left PTA was twice as frequent as right PTA, but with no statistical significance. Medial-type PTA was extremely rare. AICA arose in most PTA variants. Rarely, a lateral-type PTA gave rise to the cerebellar artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 30 publications
0
39
1
1
Order By: Relevance
“…However, two recent large studies have demonstrated 11 times higher incidence for the lateral type. 11,12) …”
Section: The Persistent Primitive Carotid-vertebrobasilar Anastomosesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two recent large studies have demonstrated 11 times higher incidence for the lateral type. 11,12) …”
Section: The Persistent Primitive Carotid-vertebrobasilar Anastomosesmentioning
confidence: 99%
“…Additionally, Uchino et al have demonstrated two lateral type PTAs, but no medial type PTA, supplying the superior cerebellar artery (neural structures) on magnetic resonance angiography (MRA). 12) Suttner et al hypothesized that the lateral and medial type PTA may be of different carotid-vertebrobasilar anastomosis origin, and that the branches of the MHT may be the remnant of the medial type PTA. 19) Some authorities support this view as well, stating that the lateral artery of the clivus is the remnant of the trigeminal artery.…”
Section: The Persistent Primitive Carotid-vertebrobasilar Anastomosesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4353] The former appears to be the most frequent variation occurring up to 11 times more often than the medial variation. [343555]…”
Section: Anatomy and Classificationmentioning
confidence: 99%
“…In magnetic resonance (MR) angiography examinations, PTA with its variants is detected in about 0.5%. Uchino et al [24] reported that out of 3626 MR angiographic examinations, 12 (0.34%) cases of PTA and 6 (0.17%) cases of PTA variants were found. Another large study examining 16,415 MR angiographies revealed that the incidence of both PTA and its variants was 0.68% [18].…”
Section: Introductionmentioning
confidence: 99%